2014
DOI: 10.1007/s00359-014-0887-1
|View full text |Cite
|
Sign up to set email alerts
|

Visual generalization in honeybees: evidence of peak shift in color discrimination

Abstract: In the present study, we investigated color generalization in the honeybee Apis mellifera after differential conditioning. In particular, we evaluated the effect of varying the position of a novel color along a perceptual continuum relative to familiar colors on response biases. Honeybee foragers were differentially trained to discriminate between rewarded (S+) and unrewarded (S-) colors and tested on responses toward the former S+ when presented against a novel color. A color space based on the receptor noise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Honeybees are models for studying how animals with relatively small brains accomplish complex cognition, displaying seemingly advanced (or ''nonelemental'') learning phenomena involving multiple conditioned stimuli. These include ''peak shift'' [1][2][3][4]-where animals not only respond to entrained stimuli, but respond even more strongly to similar ones that are farther away from non-rewarding stimuli. Bees also display negative and positive patterning discrimination [5], responding in opposite ways to mixtures of two odors than to individual odors.…”
Section: Discussionmentioning
confidence: 99%
“…Honeybees are models for studying how animals with relatively small brains accomplish complex cognition, displaying seemingly advanced (or ''nonelemental'') learning phenomena involving multiple conditioned stimuli. These include ''peak shift'' [1][2][3][4]-where animals not only respond to entrained stimuli, but respond even more strongly to similar ones that are farther away from non-rewarding stimuli. Bees also display negative and positive patterning discrimination [5], responding in opposite ways to mixtures of two odors than to individual odors.…”
Section: Discussionmentioning
confidence: 99%
“…After differential conditioning, when bees have to distinguish between two colours, their generalisation curve will be narrower, as compared to bees trained with only one colour (Giurfa 2004 ), confirming what is generally known from many other associative learning studies. Colour generalisation in honeybees can also be affected by a peak shift towards a novel colour, as shown by Martínez-Harms et al ( 2014 ). In this work the RNL model colour space was used to characterise a perceptual continuum among three colour stimuli—a training colour, an unrewarded alternative colour and a novel colour that was similar to (but discriminable from) the training colour.…”
Section: Behavioural Functions Of Colour Vision In Beesmentioning
confidence: 86%
“…It is particularly interesting in the context of pollination, where it could have a significant impact on the evolution of flower colours by influencing pollinator-induced selection for discriminable colours (Lynn et al 2005 ; Martínez-Harms et al. 2014 ).…”
Section: Behavioural Functions Of Colour Vision In Beesmentioning
confidence: 99%
“…Perales et al [8] found that suitable spectral optimization could clearly enhance the vision of color deficient by comparing the Rosch-MacAdam color volume for color-deficient observers rendered by three of these singular spectra. Martínez-Harms et al [9] revealed the occurrence of peak shift in the color vision of honeybees and indicated that honeybees can learn color stimuli in relational terms based on chromatic perceptual differences. Souza et al [10] used the Cambridge Color Test (CCT) to investigate the influence on color discrimination thresholds due to the number of luminance levels present in the luminance noise.…”
Section: Current Color Discrimination Systemmentioning
confidence: 99%